Methods of non-[alpha]-amino acid synthesis - Smith, Michael, 1946 October 17- (CRC Press, 2014)
"Amino acids are the building blocks of proteins. The most common are alpha-amino acids based on their molecular structures, but other structures are possible (such as beta and gamma). Most books on amino acids focus on alpha-amino acids, but this book describes the many other amino acids, many of which are also critically important in biology. In addition, non-alpha-amino acids are used as chiral ligands in many catalysis reactions and are useful starting materials for the synthesis of important natural and non-natural products"--